CARBON SEQUESTRATION IN RELATION TO TREE COMPOSITION IN WAWA ZANGE FOREST RESERVES, GOMBE STATE, NIGERIA - MUHAMMED BASHIR , BELLO; MUHAMMAD AUWAL, NAFISAT (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2013)
The study examined carbon dioxide (CO2) sequestration in relation to trees composition in Wawa-Zange Forest Reserve Gombe State. Twenty (20) sample plots of (50X50m) were systematically laid at 100m interval in order to carry out tree survey. Simpson’s Diversity Index and non-destructive biomass estimation technique were employed (allometric equation) to determine the volume of carbon in Above-Ground Biomass. A total of 192 individual trees encountered in the forest with Parkia biglobosa and Gmelina arborea as the most widely distributed and the least distributed trees respectively. The result also indicated that Gmelina arborea has the highest CO2 sequestration potential (2,860,00kg) while Ximenia Americana (339,36kg) has the lowest CO2 sequestration potential. The study further revealed that the sampled plots in Wawa-zange forest reserve has the potential of storing 362.57tC/ha and total of 20,340,177 tonnes of carbon throughout its existence. Regression analyses indicated that both girth and Diameter at Breath Height (DBH) of trees have a positive relation (r=0.9) with carbon sequestration rate of tree species. The study recommended that government should put more efforts towards forest protection through effective monitoring within and outside the forest reserve. The study recommended that government should establish a guide on the type of tree species that should be planted for carbon capture for effective sequestration purpose.